2023
DOI: 10.1002/advs.202205345
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc Transporter SLC39A10 Plays an Essential Role in Embryonic Hematopoiesis

Abstract: The role of zinc in hematopoiesis is currently unclear. Here, SLC39A10 (ZIP10) is identified as a key zinc transporter in hematopoiesis. The results show that in zebrafish, Slc39a10 is a key regulator of the response to zinc deficiency. Surprisingly, both slc39a10 mutant zebrafish and hematopoietic Slc39a10-deficient mice develop a more severe form of impaired hematopoiesis than animals lacking transferrin receptor 1, a well-characterized iron gatekeeper, indicating that zinc plays a larger role than iron in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Finally, our study has several limitations that should be addressed. First, although we propose that hyperactivated P53‐induced apoptosis plays an essential role in hematopoietic malfunctions, other cell death signaling pathways, such as necroptosis 63 and ferroptosis, 64 may also contribute to this complex pathological process. Exploring the interplay among different forms of cell death in hematopoietic disorders is an interesting avenue for future investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, our study has several limitations that should be addressed. First, although we propose that hyperactivated P53‐induced apoptosis plays an essential role in hematopoietic malfunctions, other cell death signaling pathways, such as necroptosis 63 and ferroptosis, 64 may also contribute to this complex pathological process. Exploring the interplay among different forms of cell death in hematopoietic disorders is an interesting avenue for future investigation.…”
Section: Discussionmentioning
confidence: 96%
“… 49 Interestingly, it has been shown that zinc has a more significant role in hematopoiesis than iron, at least in early hematopoietic stem cells. 50 In immune function-related signaling, zinc enhances the development of regulatory T cells, as induced by the transcription factor Foxp3. 51 , 52 On the other hand, excessive intracellular zinc accumulation can lead to apoptosis.…”
Section: Regulation Of Cellular Zinc Signalingmentioning
confidence: 99%
“… 185 ZIP10 Hematopoietic disease Downregulated Targeting ZIP10 may be a new therapeutic strategy against early fetal anemia. 50 ZIP14 Dystrophic muscles Upregulated Underscores the importance of regulated zinc homeostasis in metastatic cancer-induced muscle dystrophy and suggests a novel treatment avenue by targeting ZIP14. 50 Liver cirrhosis Upregulated A new potential therapeutic avenue for preventing iron-death-induced liver fibrosis.…”
Section: Therapeutic Targets For Cellular Zinc Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian cells, zinc homeostasis is tightly regulated by two families of zinc transporters, namely solute carrier family 30 (Slc30a, also known as ZnTs) and solute carrier family 39 (Slc39a, also known as ZIPs), which export and import cellular zinc, respectively. Zinc imbalance caused by dysfunction of zinc transporters contributes to impairment of several important functions, such as hematopoiesis and macrophage survival (He et al, 2023;Gao et al, 2017). Slc30a1 (ZnT1) is ubiquitously expressed in mammalian cells and is localized primarily at the plasma membrane (Nishito and Kambe, 2019;Golan et al, 2015;Guo et al, 2010), where it helps maintain cellular zinc homeostasis by exporting cytoplasmic zinc to the extracellular space (Shusterman et al, 2017, Kambe et al, 2015, Kimura and Kambe, 2016.…”
Section: Introductionmentioning
confidence: 99%